Cultivation of Scenedesmus dimorphus with domestic secondary effluent and energy evaluation for biodiesel production - Zhang, S S (Environmental technology, 2015)
Microalgae cultivation in wastewater has gained significant attention as a cost-saving means for algae-based biofuel production. To evaluate the performance of Scenedesmus dimorphus cultivated in a 100-L continuously operated photobioreactor using domestic secondary effluent (DSE), algal growth, nutrients removal and energy evaluation were conducted in four scenarios. Prior to the application of continuous cultivation, S. dimorphus was grown in a batch operated 1.5-L bubble column photobioreactor to test the growth feasibility and lipids accumulation of S. dimorphus in DSE. The highest biomass achieved in DSE was 244 mg L(-1)with lipid content at 26.06%. Simultaneously, 98.72% of total phosphorus (TP) and 98.04% of total nitrogen (TN) in DSE were removed. Then, S. dimorphus were inoculated in the 100-L continuously operated photobioreactor using BG11, unsterilized DSE, N, P-added DSE and UV-sterilized DSE as the medium, respectively. Results showed that the highest biomass gained were 567, 174, 276 and 198 mg L(-1), respectively. TP removal rates in four scenarios were all above 90%. With adjustment to DSE, the overall TN removal rates increased up to 80%. Finally, energy evaluation demonstrated that although the case of BG11 as the medium provided the most energy production, the case using DSE with N and P supplementation was of the highest net energy rate, suggesting that microalgae cultivation for biodiesel production by DSE is of obvious potential and advantage over the synthesis medium like BG11